Better understanding of biomolecules as drug target: a literature review - Aida Nur Fadhilah; Yohanes Surya Jati; Diyah Novi Sekarini; Laelatul Afifah; Paula Natasha Arincy Shellaginella Vierin; Ruri Fitriyani (Indonesian Journal of Pharmacology and Therapy, 2025)
Drugs are small biological therapeutic agents that play a crucial role in enhancing human health. They have been widely used in the treatment of various diseases, with conventional medicine being one of the most common approaches. However, conventional medicine has several limitations, including non-specific drug targeting, limited efficacy, low stability, poor absorption rates, and degradation due to enzymatic activity and low pH in the digestive system. Efforts to improve drug targeting have led to the development of molecular-based therapies, particularly through the use of biomolecules as drug targets. Drug targeting aims to optimize therapeutic effects by focusing on specific targets while minimizing side effects. This review article explores research findings from the PubMed database, applying specific inclusion and exclusion criteria. It discusses the types of drugs and biomolecular targets, including G protein-coupled receptors (GPCRs), enzymes, ion channel receptors, and DNA, as well as the mechanisms through which drugs interact with these targets in the treatment of various diseases. Additionally, the advantages and disadvantages of these biomolecular targets are examined. In conclusion, the four biomolecules discussed each present unique characteristics as drug targets, highlighting the importance of carefully selecting appropriate molecules based on an understanding of their functions, properties, and interactions with drugs in the body.